2008
DOI: 10.1007/s00381-008-0617-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute cholecystitis complicating ventriculo-peritoneal shunting: report of a case and review of the literature

Abstract: A Staphylococcus epidermidis was isolated both from the ventricular catheter and CSF and from the subphrenic abscess and the gallbladder. To our knowledge, this is the first report of cholecystitis evolving as a descending shunt infection. The current literature related with this unique complication is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…26 The first hypothesis of Farfan et al 9 was that there is a relationship between FT and the development of LDH, but no final conclusion was made after clinical tests. 4,5,12 Trauma is the main cause of LDH in adolescents, 2,22,25 which is different from that in adults. 28 A recent finite element research study confirmed that FT could make the corresponding segment more vulnerable to external movements or anterior shear force.…”
mentioning
confidence: 99%
“…26 The first hypothesis of Farfan et al 9 was that there is a relationship between FT and the development of LDH, but no final conclusion was made after clinical tests. 4,5,12 Trauma is the main cause of LDH in adolescents, 2,22,25 which is different from that in adults. 28 A recent finite element research study confirmed that FT could make the corresponding segment more vulnerable to external movements or anterior shear force.…”
mentioning
confidence: 99%
“…Martínez-Lage et al reported the laparoscopic cholecystectomy for a patient who presented with acute calcular cholecystitis with prior VP shunt. No ICP monitoring was used and the patient had unremarkable postoperative course [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not reported, Demetriades et al also remark that cholecystitis can potentially yield ascending and descending VCS infections [56] as it has been observed in VP shunts [40].…”
Section: Specific Vcs Complicationsmentioning
confidence: 99%